2019
DOI: 10.1002/jia2.25272
|View full text |Cite
|
Sign up to set email alerts
|

Viral suppression among children and their caregivers living with HIV in western Kenya

Abstract: Introduction Despite the central role of caregivers in managing HIV treatment for children living with HIV , viral suppression within caregiver–child dyads in which both members are living with HIV is not well described. Methods We conducted a retrospective analysis of children living with HIV <15 years of age and their caregivers living with HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
5
25
3
Order By: Relevance
“…Among children who had a recent viral load, almost one-third of children experienced virological non-suppression in their first years on ART. This corresponds with recent studies (2017-2019) from low-and middle-income countries (LMICs) (28-38%) (5,(17)(18)(19)(20)(21)(22). However, two systematic reviews (both 20%) (22,23) and other studies have found lower proportions of virological non-suppression in children, including 12% in Ethiopia (6), 18% in South Africa (15) and 20% in Thailand (24).…”
Section: Discussionsupporting
confidence: 87%
“…Among children who had a recent viral load, almost one-third of children experienced virological non-suppression in their first years on ART. This corresponds with recent studies (2017-2019) from low-and middle-income countries (LMICs) (28-38%) (5,(17)(18)(19)(20)(21)(22). However, two systematic reviews (both 20%) (22,23) and other studies have found lower proportions of virological non-suppression in children, including 12% in Ethiopia (6), 18% in South Africa (15) and 20% in Thailand (24).…”
Section: Discussionsupporting
confidence: 87%
“…Here we have found strong evidence showing cART failure in the child is due to cART non-adherence and is tightly linked to cART failure in the mother. The magnitude of relationship between mother and child suppression we found is much higher than has been recently described in older children [28], showing the critical role of the mother for consistent cART administration. On exploring the factors related to rate of infant viral rebound, counterintuitively, the strongest predictive factor was a longer duration of maternal cART in pregnancy.…”
Section: Discussioncontrasting
confidence: 60%
“…Another study in Cambodia showed a relatively low viral suppression rate amongst adolescents compared to the adult population groups, with the viral suppression rate at 76.8% and 90% respectively [11]. In Kenya, children were more likely to be virally unsuppressed if their caregivers were not suppressed in comparison to children with caregivers that were virally suppressed [12]. Other associated factors with child viral non-suppression in children as stated in the study include younger child age at ART initiation and child tuberculosis treatment at the time of the viral load assay [13] Treatment for children and adolescents also presents several challenges including the complexity in ART dosing and the need to adjust doses as the child grows, which may be a problem especially for providers who are not skilled enough with children care or too busy to track the suppression status, which is not an uncommon scenario in low-resource settings where the paucity of healthcare workers is very signi cant [14].The associated factors of poor viral suppression in these patient group have not been well explored in secondary health care setting in Nigeria and it is important to elicit them with a view to utilizing the ndings to mitigate this.…”
Section: Introductionmentioning
confidence: 99%